study The effect of dry bread yeast Saccharomyces cerevisiae, in some qualities of vegetative growth and nutritional status of the faba bean Vicia fabd - Afrah M. Al-Dhalimi; Salewa H. Hussein; Qawther K. Gibbren; Asel K. Abdul-Hussein; Zaineb S. Abas (Al-Qadisiyah Journal of Pure Science, 2018)
The study was conducted in Zuhair's nursery, which is one of the private nurseries in the province of Najaf for the duration of 10/10/2015 until 15/12/2015, so as to test the viability of dry bread yeast on  vegetative growth and internal nutritive content of faba bean plants>The plants where treated after 20 days from sowing by concentrations (0.5, 10) g / L of yeast solution and by  foliar application or glaucoma around roots and method of integration between by tripled separates the one and the other 10 days.Results of the study showed that there are significant differences in the studied growth indicators and characteristics of leaves inner chemical of plants treated different concentrations and with all the methods used compared with plants is not treated with a solution of yeast . As noted by the results that the highest rate in the traits of the stem has reached (44.03 cm, 6.58 cm; 11.0) for the length of the stem and the length of the internodes and the number of nodes respectively, in the plants treated by spray and glaucoma around roots with 5 g / L.With regard to the characteristics of the stem, the results pointed to the positive effect of the dry bread yeast solution which reported significant differences in the characteristics of leaves, compared with the control treatment and the highest rate of the number of leaflets, and leaf area, and the content of total chlorophyll was (25.00, 10.844 cm 2, 153.69 mg / 100 g wet weight ) respectively when plants treated  by spray and glaucoma around roots together with 5 g / l, as well as in fresh and dry weight  where this treatment gave the highest average (0.464 g, 0.03800 g) and respectively.The results also indicated thst there were significant differences in the chemical characteristics of the leaves when treated with a solution of dry bread yeast, where the treatment of overlapping recorded between spraying and glaucoma around the roots with 5 g / l higher rate to the percentage of nitrogen, phosphorus and potassium were 3.09 and 2.69 and 1.25 respectively, in the amount of total carbohydrates and proteins, reaching its highest level at which the transaction amounted to 8.876 and 16.89 respectively